Ocimum sanctum Linn. as a natural source of skin anti-ageing compounds - Wantida Chaiyana (2018)
© 2018 Elsevier B.V. Ocimum sanctum Linn., widely used in food preparation, has been reported for several biological beneficial activities and thus potential for treatment of various health conditions. However, the biological activities related to skin anti-ageing, including anti-collagenase, anti-elastase, and anti-hyaluronidase activities, have not been reported so far. Therefore, this study aimed to investigate the skin anti-ageing activity of O. sanctum extracts. The aerial part of O. sanctum was extracted by fractionated extraction using n-hexane, ethyl acetate, and ethanol, respectively. Rosmarinic acid and total phenolic content was investigated. Antioxidant activity was determined by in vitro methods. Anti-inflammatory activity was investigated according to the inhibition of nuclear factor kappa B (NF-κB) expression and interleukin-6 (IL-6) secretion. The anti-ageing activity was investigated by in vitro inhibition of collagenase, elastase, and hyaluronidase activities. The ethanolic extract of O. sanctum, which had the highest yield (6.5%), contained the highest rosmarinic acid (19.3% w/w) and the highest total phenolic content (50.2 ± 0.6 mg gallic acid/g sample). Additionally, it possessed the most potent antioxidant activity with the Trolox equivalent antioxidant capacity of 270.1 ± 15.1 μM/mg, equivalent concentration of 459.3 ± 91.4 μM/mg, and inhibition against 2, 2-diphenyl-1-picrylhydrazyl radical of 34.0 ± 0.7%. The ethanolic extract also showed the highest anti-inflammatory activity with the inhibition against IL-6 secretion and NF-κB expression of 54.7 ± 3.1% and 79.3 ± 9.6%, respectively. Moreover, it also exerted the highest inhibition against matrix metallopeptidase-1 and hyaluronidase with the inhibition of 77.7 ± 9.0% and 98.1 ± 0.1%, respectively. Rosmarinic acid was found as the major compound responsible for those anti-ageing activities. Therefore, the ethanolic extract of O. sanctum is an attractive natural source of anti-skin ageing ingredient for further applications in cosmetic and/or cosmeceutical industry.